Vrednost kombinovanog otkrivanja specifičnih imunoglobulina E, interleukin-6 i regulatornih T ćelija u predviđanju rizika od postoperativnog ponavljanja kod pacijenata sa eozinofilnim hroničnim sinusitisom i nazalnim polipima: Predicting Postoperative Recurrence in Eosinophilic Sinusitis with Biomarkers - Gao, Xudong; Zhang, Jin; Li, An; Ding, Yu; Zhao, Bo; Wang, Yujuan (Journal of Medical Biochemistry, 2024)
Background: To investigate the predictive value of specific immunoglobulin E (sIgE), interleukin-6 (IL-6) and regulatory T cells (Treg) on the risk of postoperative recurrence in patients with eosinophilic chronic sinusitis with nasal polyps (EcRswNP).Methods: A total of 198 patients with EcRswNP collected to our Hospital from January 2019 to December 2021 were selected as the research subjects. All patients underwent functional endoscopic sinus surgery. The patients were selected to recurrence group (RG, n = 48) and non-recurrence group (NRG, n = 150) on the basis of the recurrence after 1 year of follow-up. The related factors of postoperative recurrence of EcRswNP were analyzed.. The ROC was used to analyze the dangerous of sIgE, IL-6 and Treg in predicting postoperative recurrence of EcRswNP patients.Results: The proportion of asthma patients, nasal congestion VAS score and peripheral blood Eos% content in the RG were exceed than the NRG, and the Organization Neu % and peripheral blood Neu% levels were less than those in the NRGp (P all < 0.05). The serum sIgE and serum IL-6 in the RG were exceed than the NRG, and the level of peripheral blood Treg was less than the NRG (P < 0.05). Logistic regression analysis showed that high levels of serum sIgE, serum IL-6 and low Treg levels were risk factors for postoperative recurrence (P < 0.05). ROC showed that the AUC of peripheral blood sIgE level, IL-6 and Treg levels alone in predicting the dangerous of postoperative recurrence in patients with EcRswNP were 0.786, 0.707 and 0.636, respectively (all P < 0.05); The AUC of combined prediction of peripheral blood sIgE, IL-6 and Treg levels for postoperative recurrence dangerous in patients with EcRswNP was 0.973, indicating that the efficacy of jointed prediction was exceed than that of single prediction (P < 0.05).Conclusions: The high levels of sIgE, IL6 and low Treg levels in patients with EcRswNP before operation will increase the risk of postoperative recurrence, which is a risk factor affecting postoperative recurrence, and the three indicators have good predictive value for predicting postoperative recurrence in patients with EcRswNP, and the combination of the three indicators has better value in predicting postoperative recurrence.